Bombay cinema's Islamicate histories - Bhaskar, Ira; Allen, Richard, 1959- (Intellect Books, 2022)
Popularly known as Bollywood, Bombay cinema conjures up song, dance and starry-eyed romance. Where do those conventions come from? Many derive from the historical influence of Muslim cultures interacting with other traditions in the Indian subcontinent. Contributions by major scholars of South Asian cultural history and Indian Cinema 105 b&w illus.